Continued Intention to Use UCOM: Four Factors for Integrating With a Technology Acceptance Model to Moderate the Satisfaction of Learning - Tawafak, Ragad M.; Awanis, Romli; Ruzaini, Abdullah Arshah (IEEE, 2018)
This paper investigates whether the universities’ communication model and the technology acceptance model, which include four factors, namely, academic performance, student satisfaction, effectiveness, and support assessment, simultaneously enhance student satisfaction and improve the teaching method and academic performance level. This paper aims to adapt a model to improve the assessment method and improve the model of student satisfaction. This paper focuses on improving e-learning to activate the feedback of continued intention of using the model that helps to navigate the student understanding level and academic performance immediately. In this paper, surveys were distributed to (295) undergraduates in four universities in Oman to assess their feedback on e-learning. The partial least squares-structural equation model was used to calculate the measurement of all hypotheses proposed. The results of this paper prove that most of the hypotheses are a positive influence on the continuance of intention to use the proposed model.